Elevated plasma RANTES in fibrodysplasia ossificans progressiva – A novel therapeutic target?. (October 2019) - Grgurević, Lovorka; Novak, Ruđer; Trkulja, Vladimir; Hamzić, Lejla Ferhatović; Hrkač, Stela; Grazio, Simeon; Santini, Marija
Abstract: Fibrodysplasia ossificans progressiva (FOP) is a rare hereditary disease caused by a mutation in the intracellular domain of the activin A receptor type I and is characterized by episodes (flare-ups) of progressive heterotopic endochondral ossification (HO) in the soft tissues. The mutation alone is not sufficient for the occurrence of HO since flare-ups are triggered by inflammation and activation of the innate immune system. A number of cellular and humoral mediators have been implicated in animal and in vitro models. Observations in humans support the inflammatory nature of the condition, but data on the involved mediators are variable. We hypothesize that for induction of flare-ups in patients with FOP increase in at least one of the pro-inflammatory cytokines is both essential and sufficient to trigger the entire process of the inflammatory cells influx resulting in the novel ectopic bone formation and we suggest that C–C motif ligand 5 (CCL5), a pro-inflammatory chemokine also known as Regulated on activation, normal T-cell expressed and secreted (RANTES), might be the key candidate. CCL5 is a chemoattractant for all cellular types implicated in HO and is produced by the cells of the tissue microenvironment at the sites of HO as well as by the pro-inflammatory cellular mediators. CCL5 induces ossification in cultured human pluripotent mesenchymal cells (hMSCs) and in the primary culture of monocytes from FOP patients (but not from their healthy relatives), stimulation with lipopolysaccharide induces CCL5 expression. Finally, in a pilot study we used a panel of 23 cytokines and chemokines to screen the plasma samples of three subjects: a female patient with FOP during a flare-up; a female patient with hyperostosis corticalis generalisata (van Buchem disease), another rare disease characterized by excessive bone formation at the sites where it regularly occurs that does not include inflammatory events; and a healthy woman without bone disorders. There appeared a rather clear-cut signal of a 2-fold higher level of CCL5 in the FOP patient vs. the healthy subject and the van Buchem patient. Evaluation of the hypothesis would require an international prospective study, with main motivation being the lack of a conclusive treatment as the major unmet need in FOP. A treatment targeting CCL5 receptor already exists and is used in HIV-infected patients.